2016
DOI: 10.1177/0306624x16668175
|View full text |Cite
|
Sign up to set email alerts
|

Sex Offending and Situational Motivation

Abstract: Sex offending is typically understood from a pathology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 68 publications
(86 reference statements)
0
12
0
Order By: Relevance
“…Two theories discussed in this paper suggest the following approaches to the JK business; 1) Gendered pathways theory allows related agencies to provide female minors with adequate help that meet their survival needs based on female characteristics, and 2) Sexual script theory intervenes sexual offenses by identifying social and psychological push factors of creating distorted sexual predilections (Farmer et al, 2016;Salisbury, 2007;Wiederman, 2015). Sexual Sexual exploitations of minors in the "JK business" settings require the immediate attention of researchers as the businesses continue to expand and victimize vulnerable teenagers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two theories discussed in this paper suggest the following approaches to the JK business; 1) Gendered pathways theory allows related agencies to provide female minors with adequate help that meet their survival needs based on female characteristics, and 2) Sexual script theory intervenes sexual offenses by identifying social and psychological push factors of creating distorted sexual predilections (Farmer et al, 2016;Salisbury, 2007;Wiederman, 2015). Sexual Sexual exploitations of minors in the "JK business" settings require the immediate attention of researchers as the businesses continue to expand and victimize vulnerable teenagers.…”
Section: Resultsmentioning
confidence: 99%
“…Stigmatization can worsen the girls' attitude toward authorities and rebel against them to commit more crimes or become more involved in the "JK businesses." Sexual script theory demonstrates cultural messages in society as a source of distorted moral behaviors and deviant sexuality (Farmer et al, 2016;Frith & Kitzinger, 2001). An advantage of using sexual script theory is to be able to take two different approaches to crime; sociology and cognitive psychology (Frith & Kitzinger, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study also brought new insight and theoretical perspectives to the existing body of knowledge on the commission of sexual exploitation by international peacekeepers in host countries. Beauregard and Leclere (2007) and Farmer et al (2016) approached the study on sex offending from the pathological and personal perspectives. However, this research brought new ideas by approaching the study from the perspectives of rational choice and routine activities theories.…”
Section: Susceptabilities Of Locals To Sexual Explotation By Peacekeementioning
confidence: 99%
“…Past researchers (Beauregard & Leclere, 2007;Farmer, McAlinden, & Maruna, 2016) have used different research methods and theoretical models to study sex offenses but not within the peacekeeping contexts. Farmer et al (2016) used routine activities theory to explore situational motivation and how offenders could desist from sexual offending while Beauregard and Leclere (2007) used rational choice theory to explore sex offending and decision-making processes of sex offenders. These research methods and theoretical models demonstrated that environmental or situational factors could trigger action by sex offenders and that offenders exhibit a rational behavior in deciding to commit or not to commit a sex offense.…”
Section: Introductionmentioning
confidence: 99%